Younger Dryas to early Holocene (12.9 to 8.1 ka) limnological and hydrological change at Barley Lake, California (northern California Coast Range). (September 2021) - Leidelmeijer, Jenifer A.; Kirby, Matthew E.C.; MacDonald, Glen; Carlin, Joseph A.; Avila, Judith; Han, Jiwoo; Nauman, Benjamin; Loyd, Sean; Nichols, Kevin; Ramezan, Reza
Abstract: Paleoperspectives of climate provide important information for understanding future climate, particularly in arid regions such as California, where water availability is uncertain from year to year. Here, we present a record from Barley Lake, California, focusing on the interval spanning the Younger Dryas (YD) to the early Holocene (EH), a period of acute and rapid global climate change. Twelve radiocarbon dates constrain the timing between 12.9 and 8.1 ka. We combine a variety of sediment analyses to infer changes in lake productivity, relative lake level, and runoff dynamics. In general, the lake is characterized by two states separated by a <200-year transition: (1) a variably deep, lower-productivity YD lake; and (2) a two-part variably shallow, higher-productivity EH lake. Inferred EH winter-precipitation runoff reveals dynamic multidecadal-to-centennial-scale variability, in agreement with the EH lake-level data. The Barley Lake archive captures both hemispheric and regional signals of climate change across the transition, suggesting a role for both ocean-atmosphere and insolation forcing. Our paleoperspective emphasizes California's sensitivity to climate change and how that change can generate abrupt shifts in limnological regimes.